Synthesis method of phosphorus-containing polysilazane and prepared zinc-rich anti-corrosion coating

By adopting the synthesis method of phosphorus-containing polysilazane and the preparation method of single-component zinc-rich coating, the problem of large corrosion-resistant coating thickness and poor corrosion resistance on the surface of carbon steel is solved, and high adhesion and salt resistance are achieved Excellent fog performance and extended opening time coating effect.

CN119390985APending Publication Date: 2025-02-07HANGZHOU XINGXIANGLI TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411690714.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the corrosion-resistant coating on the surface of carbon steel is thicker, but it is impossible to achieve corrosion resistance of more than 600 hours. The commonly used two-component coating has a short opening time and is difficult to construct.

Method used

Using a synthesis method of phosphorus-containing polysilazane, the phosphorus-containing polysilazane solution is obtained by dissolving solid methylhydropolysilazane into an organic solvent, adding phosphate ester and Caster catalyst, and heating reaction is carried out. , and combined with fiber powder, zinc powder, etc., to prepare a single-component zinc-rich anti-corrosion coating.

Benefits of technology

It realizes a thinner anti-corrosion coating, excellent adhesion and salt spray resistance, and has a longer opening time. It can prepare a single-component zinc-rich coating, which improves the strength and salt spray corrosion resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005150859090000091
    Figure BDA0005150859090000091
  • Figure BDA0005150859090000101
    Figure BDA0005150859090000101
  • Figure FDA0005150859080000011
    Figure FDA0005150859080000011
Patent Text Reader

Abstract

The invention discloses a synthesis method of phosphorus-containing polysilazane. The synthesis method comprises the following steps: S1, preparing solid methyl hydrogen polysilazane; s2, solid methyl hydrogen polysilazane is dissolved in an organic solvent, phosphate ester is added, the mixture is stirred to be uniform, then a Karst catalyst is added, and a phosphorus-containing polysilazane solution is obtained after a heating reaction. The phosphorus-containing polysilazane solution obtained through combined action of polysilazane and phosphate containing a vinyl structure is applied to an anti-corrosion coating, the anti-corrosion coating with the thin thickness can be obtained, and the adhesive force and the salt spray resistance are excellent. According to the invention, self-made phosphorus-containing polysilazane is adopted, phosphate is connected to polysilazane through chemical modification, the salt spray resistance effect is improved, the storage stability is good, phosphorus liquid passivation treatment is not needed, and the process is green and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to C09D and the field of coating compositions, and in particular to a method for synthesizing phosphorus-containing polysilazane and a prepared zinc-rich anticorrosion coating. Background Art

[0002] Carbon steel is a high-strength steel material that is widely used in infrastructure construction. However, carbon steel has poor corrosion resistance, and conventional anti-corrosion coatings are prone to corrosion and peeling. In the prior art, the method of first applying a primer and then applying a topcoat is usually adopted to improve the corrosion resistance and salt spray resistance, but the coating process is cumbersome. It is also possible to first perform a phosphorus passivation treatment on the carbon steel surface and then apply the coating, but the phosphating wastewater pollutes the environment greatly and cannot be widely used. In addition, the thickness of the corrosion-resistant layer on the surface of carbon steel on the market is relatively thick, and it is still impossible to achieve a corrosion-resistant effect of more than 600 hours. Commonly used corrosion-resistant coatings are mostly two-component, with a short open time and difficult to construct. Therefore, it is crucial to develop a single-component zinc-rich anti-corrosion coating for use on carbon steel surfaces.

[0003] Chinese invention patent CN115141501B discloses a chromium-free Dacromet coating that prevents detachment, its preparation, and a coating process on the surface of bolts, which improves the mesh structure between zinc and aluminum, makes the carbonization of the chromium-free Dacromet coating more complete, makes the topcoat more closely attached to the basecoat, avoids leakage of the basecoat after the topcoat is applied, and improves the adhesion of the chromium-free Dacromet coating, but the neutral salt spray test time is only 800h. Chinese invention patent CN110982428B discloses a zinc-aluminum anticorrosion coating based on polysilazane, and the zinc-aluminum coating prepared from the zinc-aluminum anticorrosion coating based on polysilazane has good adhesion, excellent high temperature resistance, and long salt spray resistance. However, there are amine groups in the molecular structure of polysilazane, which have high alkalinity and are easy to react with zinc powder to form zinc hydroxide when compounded with zinc powder. The coating has a short open time and cannot be prepared into a single-component coating. Summary of the invention

[0004] In order to develop a single-component zinc-rich anti-corrosion coating, the first aspect of the present invention provides a method for synthesizing phosphorus-containing polysilazane, comprising the following steps:

[0005] S1 prepares solid methyl hydrogen polysilazane;

[0006] S2: dissolving solid methyl hydrogen polysilazane in an organic solvent, adding phosphate and stirring evenly, then adding a Custer catalyst, and heating the reaction to obtain a phosphorus-containing polysilazane solution.

[0007] As a preferred embodiment, the temperature of the heating reaction in step S2 is 70-90° C., and the reaction time is 50-70 min.

[0008] As a preferred embodiment, the heating reaction temperature in step S2 is 80° C. and the reaction time is 60 min.

[0009] As a preferred embodiment, the phosphate ester is a vinyl-containing phosphate ester, and the molecular structural formula of the vinyl-containing phosphate ester is: In the structural formula: R1 is an alkyl group or a hydrogen atom, R2 is an alkyl group or a hydrogen atom, and R3 is R4 is an alkyl group, R5 is an alkyl group or a hydrogen atom, and R6 is an ether bond or an alkane.

[0010] As a preferred embodiment, the vinyl-containing phosphate ester includes but is not limited to hydroxyethyl methacrylate phosphate, polyethylene glycol methacrylate phosphate, vinyl phosphate, and phosphoric acid dimer.

[0011] As a preferred embodiment, the organic solvent is selected from at least one of ethyl acetate, methyl acetate, butyl acetate, toluene, butylbenzene and xylene.

[0012] As a preferred embodiment, the weight ratio of the solid methyl hydrogen polysilazane to the phosphate ester is 100:(1-20).

[0013] As a preferred embodiment, the weight ratio of the solid methyl hydrogen polysilazane to the phosphate ester is 100:(1-10).

[0014] As a preferred embodiment, the weight ratio of the solid methyl hydrogen polysilazane to the phosphate ester is 100:(1-5).

[0015] As a preferred embodiment, the weight ratio of the solid methyl hydrogen polysilazane to the phosphate ester is 100:3.

[0016] As a preferred embodiment, the specific preparation steps of the solid methyl hydrogen polysilazane in step S1 are as follows: dissolving chlorosilane containing silicon hydrogen in a solvent to form a 1-10wt% solution, introducing ammonia at a certain speed, circulating the reaction, controlling the reaction temperature to 0-30°C, reacting for 8-12h, filtering out the by-product ammonium chloride, and obtaining an alkyl hydrogen silazane oligomer solution; then adding a polymerization catalyst, reacting at 90-110°C for 20-30h, removing the solvent by distillation under reduced pressure, and cooling to room temperature to obtain solid methyl hydrogen polysilazane.

[0017] As a preferred embodiment, the specific preparation steps of the solid methyl hydrogen polysilazane in step S1 are as follows: dissolving chlorosilane containing silicon hydrogen in a solvent to form a 5wt% solution, introducing ammonia at a certain speed, circulating the reaction, controlling the reaction temperature to 0-30°C, reacting for 10 hours, filtering out the by-product ammonium chloride, and obtaining an alkyl hydrogen silazane oligomer solution; then adding a polymerization catalyst and reacting at 100°C for 24 hours, removing the solvent by distillation under reduced pressure, and cooling to room temperature to obtain solid methyl hydrogen polysilazane.

[0018] As a preferred embodiment, the polymerization catalyst is at least one selected from tetrabutylammonium chloride, triruthenium dodecacarbonyl, ruthenium hydroxide, ruthenium trichloride, benzyl lithium, and potassium borohydride.

[0019] As a preferred embodiment, the silicon hydrogen-containing chlorosilane is selected from at least one of methyl hydrogen dichlorosilane, dimethyl dichlorosilane, and vinyl methyl dichlorosilane.

[0020] As a preferred embodiment, the solvent includes but is not limited to ethyl acetate, methyl acetate, butyl acetate, toluene, butylbenzene, and xylene.

[0021] As a preferred embodiment, the flow rate of the ammonia gas is 1-3m 3 / h. Preferably, the flow rate of the ammonia is 2m 3 / h.

[0022] As a preferred embodiment, after adding the Custer catalyst in step S2, the Pt content is 300 ppm.

[0023] The second aspect of the present invention provides a one-component zinc-rich anti-corrosion coating, wherein the raw materials for preparing the coating include phosphorus-containing polysilazane prepared by the above-mentioned method for synthesizing phosphorus-containing polysilazane.

[0024] As a preferred embodiment, the raw materials for its preparation include, by weight: 90-110 parts of phosphorus-containing polysilazane solution, 5-20 parts of fiber powder, 320-360 parts of zinc powder, 5-15 parts of silicon dioxide, 5-10 parts of anti-settling agent, 1-5 parts of defoaming agent, 1-5 parts of dispersant, and 1-5 parts of leveling agent.

[0025] As a preferred embodiment, the raw materials for its preparation include, by weight: 95-115 parts of phosphorus-containing polysilazane solution, 10-15 parts of fiber powder, 330-350 parts of zinc powder, 5-10 parts of silicon dioxide, 5-8 parts of anti-settling agent, 1-3 parts of defoaming agent, 1-3 parts of dispersant, and 1-3 parts of leveling agent.

[0026] As a preferred embodiment, the raw materials for its preparation include, by weight: 100 parts of phosphorus-containing polysilazane solution, 10 parts of fiber powder, 340 parts of zinc powder, 8.8 parts of silicon dioxide, 6.6 parts of anti-settling agent, 2.2 parts of defoaming agent, 2.2 parts of dispersant, and 2.2 parts of leveling agent.

[0027] As a preferred embodiment, the content of polysilazane in the phosphorus-containing polysilazane solution is 40-60 wt %.

[0028] As a preferred embodiment, the content of phosphorus-containing polysilazane in the phosphorus-containing polysilazane solution is 50 wt %.

[0029] As a preferred embodiment, the fiber powder has a fiber length of 5-30 μm and a fiber diameter of 3-15 μm.

[0030] As a preferred embodiment, the elastic modulus of the fiber powder is ≥80 GPa

[0031] As a preferred embodiment, the fiber powder is selected from at least one of chopped carbon fiber powder, chopped basalt fiber powder, chopped potassium titanate whisker, chopped glass fiber powder, chopped alumina fiber powder, and chopped aluminum silicate fiber powder.

[0032] As a preferred embodiment, the fiber powder is selected from at least one of chopped carbon fiber powder, chopped glass fiber powder, and chopped aluminum silicate fiber powder.

[0033] The applicant found in the experiment that by using polysilazane and phosphate containing vinyl structure to work together, a thin anti-corrosion coating with excellent adhesion and salt spray resistance can be obtained. The possible reasons are: polysilazane contains a large number of silicon-hydrogen bonds, the molecular weight of solid polysilazane is large, the reaction steric hindrance is strong, the alkalinity after the aminolysis reaction is low, it can coexist with zinc powder for a long time, and it can react with phosphate containing vinyl structure. The phosphorus end passivates carbon steel to form a dense phosphate, and a thin corrosion-resistant layer is obtained only through the solid phosphorus-containing polysilazane structure.

[0034] The applicant further discovered that when the zinc powder content increases, the strength of the corrosion-resistant coating will decrease. The inventors can increase the content of zinc powder in the corrosion-resistant coating by introducing short-cut fibers with high elastic modulus, thereby further improving the salt spray corrosion resistance. The reason may be that short-cut fibers with high elastic modulus can form a structural framework in the coating system, increase the toughness of the system, and thus avoid precipitation of zinc powder in the coating system, resulting in a decrease in strength.

[0035] As a preferred embodiment, the particle size of the zinc powder is 450-600 mesh, and the silicon dioxide is fumed silicon dioxide with a particle size of 10-30 nm.

[0036] As a preferred embodiment, the particle size of the zinc powder is 500 mesh, and the silicon dioxide is fumed silicon dioxide with a particle size of 10-30 nm.

[0037] As a preferred embodiment, the preparation method of the single-component zinc-rich anti-corrosion coating comprises the following steps: uniformly mixing a phosphorus-containing polysilazane solution, fiber powder, zinc powder, silicon dioxide, an anti-settling agent, a defoaming agent, a dispersant, and a leveling agent according to weight parts, and dispersing for 1-3 hours to obtain the coating.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The method for synthesizing phosphorus-containing polysilazane of the present invention uses polysilazane and a phosphate containing a vinyl structure to obtain a phosphorus-containing polysilazane solution, which is applied to an anti-corrosion coating to obtain a thin anti-corrosion coating with excellent adhesion and salt spray resistance.

[0040] (2) The phosphorus-containing polysilazane obtained by the synthesis method of the phosphorus-containing polysilazane of the present invention can be compounded with a large amount of zinc powder, and the open time is prolonged, and coarse zinc hydroxide particles will not appear in a short time, so that a single-component zinc-rich coating can be prepared.

[0041] (3) The single-component zinc-rich anti-corrosion coating of the present invention can increase the content of zinc powder in the corrosion-resistant coating and improve the strength of the coating by introducing short-cut fibers with high elastic modulus, thereby further improving the salt spray corrosion resistance.

[0042] (4) The single-component zinc-rich anti-corrosion coating of the present invention has excellent adhesion to carbon steel, and the formed coating has high hardness, excellent impact resistance, and long salt spray corrosion resistance time.

[0043] (5) The single-component zinc-rich anti-corrosion coating of the present invention adopts homemade phosphorus-containing polysilazane, and phosphoric acid ester is connected to polysilazane through chemical modification, so that the salt spray resistance is improved, the storage stability is good, and no phosphorus liquid passivation treatment is required, and the process is green and environmentally friendly. DETAILED DESCRIPTION

[0044] Example 1

[0045] A method for synthesizing phosphorus-containing polysilazane comprises the following steps:

[0046] S1 Preparation of solid methylhydrogen polysilazane: 10 mol of methylhydrogen dichlorosilane was dissolved in xylene to form a 5 wt% solution. 3Ammonia gas is introduced at a flow rate of / h, and the reaction is circulated. The reaction temperature is controlled to be 20-25°C, and the reaction is carried out for 10 hours. The by-product ammonium chloride is filtered out to obtain an alkyl hydrogen silazane oligomer solution; then a polymerization catalyst is added, and the reaction is carried out at 100°C for 24 hours. The solvent is removed by distillation under reduced pressure, and solid methyl hydrogen polysilazane is obtained after cooling to room temperature;

[0047] S2: dissolving 100 parts by weight of solid methyl hydrogen polysilazane in 100 parts by weight of an organic solvent, adding phosphate and stirring evenly, adding a Custer catalyst with a Pt content of ≤300 ppm, heating at 80° C. for 60 minutes to obtain a phosphorus-containing polysilazane solution.

[0048] The organic solvent is butyl acetate, and the phosphate ester is hydroxyethyl methacrylate phosphate.

[0049] The polymerization catalyst is tetrabutylammonium chloride.

[0050] The weight ratio of the solid methyl hydrogen polysilazane to the phosphate ester is 100:3.

[0051] A single-component zinc-rich anti-corrosion coating, wherein the raw materials for its preparation include, by weight, 100 parts of phosphorus-containing polysilazane solution, 10 parts of fiber powder, 340 parts of zinc powder, 8.8 parts of silicon dioxide, 6.6 parts of anti-settling agent, 2.2 parts of defoaming agent, 2.2 parts of dispersant, and 2.2 parts of leveling agent.

[0052] The content of polysilazane in the phosphorus-containing polysilazane solution is 50wt%. (Prepared by the above process)

[0053] The fiber powder is short-cut carbon fiber powder, with a fiber length of 5-30 μm, a fiber diameter of 3-15 μm, and an elastic modulus of ≥80 GPa, purchased from Toray, model T300.

[0054] The zinc powder had a particle size of 500 mesh and was purchased from Taizhou Shenglan New Material Technology Co., Ltd.

[0055] The silicon dioxide is fumed silicon dioxide with a particle size of 16 nm, purchased from Degussa, with the brand name R972.

[0056] The anti-settling agent is BYK410, the defoaming agent is WSS980 defoaming agent, the dispersant is BYK163, and the leveling agent is Tego410.

[0057] The preparation method of the single-component zinc-rich anti-corrosion coating comprises the following steps: uniformly mixing a phosphorus-containing polysilazane solution, fiber powder, zinc powder, silicon dioxide, an anti-settling agent, a defoaming agent, a dispersant, and a leveling agent according to weight parts, and dispersing for 2 hours to obtain the coating.

[0058] Example 2

[0059] A method for synthesizing phosphorus-containing polysilazane and a single-component zinc-rich anticorrosion coating prepared therefrom, the specific implementation manner being the same as that of Example 1, except that the weight ratio of the solid methyl hydrogen polysilazane to the phosphate ester is 100:5.

[0060] Example 3

[0061] A method for synthesizing phosphorus-containing polysilazane and a single-component zinc-rich anticorrosion coating prepared therefrom, the specific implementation method is the same as that of Example 1, except that the specific preparation steps of solid methylhydrogen polysilazane in step S1 are as follows: 10 mol of methylhydrogen dichlorosilane and 10 mol of dimethyldichlorosilane are dissolved in xylene to form a solution with a total mass concentration of 5 wt %, and 2 m 3 Ammonia gas is introduced at a flow rate of / h, and the reaction is circulated. The reaction temperature is controlled at 20-25°C, and the reaction is carried out for 24 hours. The by-product ammonium chloride is filtered out to obtain an alkyl hydrogen silazane oligomer solution; then a polymerization catalyst is added, and the reaction is carried out at 100°C for 24 hours. The solvent is removed by distillation under reduced pressure, and solid methyl hydrogen polysilazane is obtained after cooling to room temperature.

[0062] The polymerization catalyst is triruthenium dodecacarbonyl.

[0063] Example 4

[0064] A method for synthesizing phosphorus-containing polysilazane and a single-component zinc-rich anticorrosion coating prepared therefrom, the specific implementation method is the same as that of Example 1, except that the specific preparation steps of solid methylhydrogen polysilazane in step S1 are as follows: 10 mol of methylhydrogen dichlorosilane and 10 mol of vinyl methyl dichlorosilane are dissolved in xylene to form a solution with a total mass concentration of 5 wt %, and 2 m 3 Ammonia gas is introduced at a flow rate of / h, and the reaction is circulated. The reaction temperature is controlled at 20-25°C, and the reaction is carried out for 24 hours. The by-product ammonium chloride is filtered out to obtain an alkyl hydrogen silazane oligomer solution; then a polymerization catalyst is added, and the reaction is carried out at 100°C for 24 hours. The solvent is removed by distillation under reduced pressure, and solid methyl hydrogen polysilazane is obtained after cooling to room temperature.

[0065] The polymerization catalyst is benzyl lithium.

[0066] Comparative Example 1

[0067] A method for synthesizing phosphorus-containing polysilazane and a single-component zinc-rich anti-corrosion coating prepared therefrom, the specific implementation manner is the same as that of Example 1, except that the homemade solid methyl hydrogen polysilazane in step S1 is replaced by a commercially available polysilazane purchased from Merck, model 1500RC.

[0068] Comparative Example 2

[0069] A method for synthesizing phosphorus-containing polysilazane and a single-component zinc-rich anti-corrosion coating prepared therefrom, the specific implementation manner is the same as that of Example 1, except that the single-component zinc-rich anti-corrosion coating is prepared by raw materials, which include, by weight: 100 parts of phosphorus-containing polysilazane solution, 0 parts of fiber powder, 340 parts of zinc powder, 8.8 parts of silicon dioxide, 6.6 parts of anti-settling agent, 2.2 parts of defoaming agent, 2.2 parts of dispersant, and 2.2 parts of leveling agent.

[0070] Comparative Example 3

[0071] A method for synthesizing phosphorus-containing polysilazane and a single-component zinc-rich anti-corrosion coating prepared therefrom, the specific implementation manner is the same as that of Example 1, except that the homemade solid methyl hydrogen polysilazane in step S1 is replaced by a commercially available polysilazane purchased from Hangzhou Wanguan, model number 3600.

[0072] Comparative Example 4

[0073] A method for synthesizing phosphorus-containing polysilazane and a single-component zinc-rich anti-corrosion coating prepared therefrom. The specific implementation manner is the same as that of Example 1, except that the single-component zinc-rich anti-corrosion coating is prepared by raw materials, which include, by weight: 100 parts of phosphorus-containing polysilazane solution, 340 parts of zinc powder, 8.8 parts of silicon dioxide, 6.6 parts of anti-settling agent, 2.2 parts of defoaming agent, 2.2 parts of dispersant, 2.2 parts of leveling agent, and 12 parts of 1500 mesh mica powder.

[0074] Comparative Example 5

[0075] A method for synthesizing phosphorus-containing polysilazane and a single-component zinc-rich anticorrosion coating prepared therefrom, the specific implementation manner is the same as that of Example 1, except that the method for synthesizing phosphorus-containing polysilazane comprises the following steps:

[0076] S1 Preparation of solid methylhydrogen polysilazane: 10 mol of methylhydrogen dichlorosilane was dissolved in xylene to form a 5 wt% solution. 3 Ammonia gas is introduced at a flow rate of / h, and the reaction is circulated. The reaction temperature is controlled to be 20-25°C, and the reaction is carried out for 10 hours. The by-product ammonium chloride is filtered out to obtain an alkyl hydrogen silazane oligomer solution; then a polymerization catalyst is added, and the reaction is carried out at 100°C for 24 hours. The solvent is removed by distillation under reduced pressure, and solid methyl hydrogen polysilazane is obtained after cooling to room temperature;

[0077] S2: 100 parts by weight of solid methyl hydrogen polysilazane is dissolved in 100 parts by weight of ethyl acetate to obtain a polysilazane solution.

[0078] A single-component zinc-rich anti-corrosion coating. The raw materials for its preparation include, by weight, 100 parts of polysilazane solution, 10 parts of fiber powder, 340 parts of zinc powder, 8.8 parts of silicon dioxide, 6.6 parts of anti-settling agent, 2.2 parts of defoaming agent, 2.2 parts of dispersant, 2.2 parts of leveling agent and 3 parts of epoxy phosphate.

[0079] Comparative Example 6

[0080] A method for synthesizing phosphorus-containing polysilazane and a single-component zinc-rich anticorrosion coating prepared therefrom, the specific implementation manner is the same as that of Example 1, except that the method for synthesizing phosphorus-containing polysilazane comprises the following steps:

[0081] S1 Preparation of solid methylhydrogen polysilazane: 10 mol of methylhydrogen dichlorosilane was dissolved in xylene to form a 5 wt% solution. 3 Ammonia gas is introduced at a flow rate of / h, and the reaction is circulated. The reaction temperature is controlled to be 20-25°C, and the reaction is carried out for 10 hours. The by-product ammonium chloride is filtered out to obtain an alkyl hydrogen silazane oligomer solution; then a polymerization catalyst is added, and the reaction is carried out at 100°C for 24 hours. The solvent is removed by distillation under reduced pressure, and solid methyl hydrogen polysilazane is obtained after cooling to room temperature;

[0082] S2: 100 parts by weight of solid methyl hydrogen polysilazane is dissolved in 100 parts by weight of ethyl acetate to obtain a polysilazane solution.

[0083] A single-component zinc-rich anti-corrosion coating, wherein the raw materials for preparation include, by weight, 100 parts of polysilazane solution, 10 parts of fiber powder, 340 parts of zinc powder, 8.8 parts of silicon dioxide, 6.6 parts of anti-settling agent, 2.2 parts of defoaming agent, 2.2 parts of dispersant, and 2.2 parts of leveling agent.

[0084] The single-component zinc-rich anti-corrosion coating was subjected to silane passivation treatment before coating the carbon steel substrate. The silane passivating agent used was the silane treating agent GT-830T produced by Foshan Guiteng New Material Technology Co., Ltd.

[0085] Passivation process: soak for 3 minutes and dry naturally for 15 minutes.

[0086] Comparative Example 7

[0087] A method for synthesizing phosphorus-containing polysilazane and a single-component zinc-rich anti-corrosion coating prepared therefrom, the specific implementation manner is the same as that of Example 1, except that the homemade solid methyl hydrogen polysilazane in step S1 is replaced by a commercially available solid polysilazane purchased from Hangzhou Qingci New Materials Technology Co., Ltd., model P11.

[0088] Performance Testing

[0089] Sample processing:

[0090] (1) Pre-treatment of Q235 carbon steel, sandblasting, meeting the standard Sa2.5;

[0091] (2) The single-component zinc-rich anti-corrosion coating prepared in Examples 1-4 and Comparative Examples 1-7 was sprayed on the treated carbon steel surface with a spraying thickness of 8-12 μm. After standing for 15 minutes, the coating was baked at 200° C. for 40 minutes and then tested.

[0092] Test items:

[0093] 1. Adhesion, according to national standard GB9286-98

[0094] 2. Pencil hardness, according to the national standard GBT 6739-2006

[0095] 3. Neutral salt spray, in accordance with national standard GB / T 6461-2002

[0096] 4. Impact test, according to national standard GB_T1732-1993

[0097] 5. Open time test: Due to the strong alkalinity of liquid polysilazane, the storage time is short when compounded with zinc powder. After dispersion, coarse particles will precipitate in a short time. The time when coarse particles precipitate can be used to judge the open time of the coating.

[0098] The test results are shown in Table 1.

[0099] Table 1

[0100]

[0101]

[0102] Conclusion: When commercially available liquid and zinc powder are mixed, coarse zinc hydroxide particles will appear in a short time, and single-component zinc-rich coatings cannot be prepared; the use of chopped fibers in the formula can improve the strength of the coating and can prepare coatings with high zinc content; whether the substrate is silanized first or conventional epoxy phosphate is added as an additive, the salt spray effect is not as good as the salt spray effect of chemically modifying the phosphate to polysilazane; even if lamellar inorganic materials are used, their toughening effect is not as good as that of high elastic modulus chopped fiber powder, and high zinc content coatings cannot be prepared.

Claims

1. A method for synthesizing phosphorus-containing polysilazane, characterized in that: The following steps are involved: S1 prepares solid methyl hydrogen polysilazane; S2: dissolving solid methyl hydrogen polysilazane in an organic solvent, adding phosphate and stirring evenly, then adding a Custer catalyst, and heating the reaction to obtain a phosphorus-containing polysilazane solution.

2. The method for synthesizing phosphorus-containing polysilazane according to claim 1, characterized in that: The phosphate ester is a vinyl-containing phosphate ester, and the molecular structural formula of the vinyl-containing phosphate ester is: In the structural formula: R1 is an alkyl group or a hydrogen atom, R2 is an alkyl group or a hydrogen atom, and R3 is R4 is an alkyl group, R5 is an alkyl group or a hydrogen atom, and R6 is an ether bond or an alkane.

3. The method for synthesizing phosphorus-containing polysilazane according to claim 1, characterized in that: The organic solvent is selected from at least one of ethyl acetate, methyl acetate, butyl acetate, toluene, butylbenzene and xylene.

4. The method for synthesizing phosphorus-containing polysilazane according to claim 1, characterized in that: The weight ratio of the solid methyl hydrogen polysilazane to the phosphate ester is 100:(1-20).

5. A single-component zinc-rich anti-corrosion coating, characterized in that: The raw materials for preparation thereof include phosphorus-containing polysilazane prepared by the synthesis method of phosphorus-containing polysilazane according to any one of claims 1 to 4.

6. The single-component zinc-rich anti-corrosion coating according to claim 5, characterized in that: The raw materials for its preparation include, by weight: 90-110 parts of phosphorus-containing polysilazane solution, 5-20 parts of fiber powder, 320-360 parts of zinc powder, 5-15 parts of silicon dioxide, 5-10 parts of anti-settling agent, 1-5 parts of defoaming agent, 1-5 parts of dispersant and 1-5 parts of leveling agent.

7. The single-component zinc-rich anti-corrosion coating according to claim 6, characterized in that: The content of phosphorus-containing polysilazane in the phosphorus-containing polysilazane solution is 40-60 wt %.

8. The single-component zinc-rich anti-corrosion coating according to claim 6, characterized in that: The fiber powder has a fiber length of 5-30 μm and a fiber diameter of 3-15 μm.

9. The single-component zinc-rich anti-corrosion coating according to claim 6, characterized in that: The fiber powder is selected from at least one of chopped carbon fiber powder, chopped basalt fiber powder, chopped potassium titanate whisker, chopped glass fiber powder, chopped alumina fiber powder, and aluminum silicate fiber powder.

10. The single-component zinc-rich anti-corrosion coating according to claim 6, characterized in that: The particle size of the zinc powder is 450-600 meshes, and the silicon dioxide is fumed silicon dioxide with a particle size of 10-30 nm.

Citation Information

Patent Citations

  • A zinc-aluminum anti-corrosion coating based on polysilazane

    CN110982428B

  • Anti-loosening chromium-free Dacromet coating, its preparation and coating process on bolt surfaces

    CN115141501B

Cited By

  • Heat-resistant and aging-resistant rubber special for automobile inner tube and preparation method of heat-resistant and aging-resistant rubber

    CN119661947A

  • Normal-temperature self-curing polysilazane coating and preparation method thereof

    CN122188523A

  • A room-temperature self-curing polysilazane coating and its preparation method

    CN122188523B